Vacancy-driven stabilization of the cubic perovskite polymorph of CsPbI3 - Kye, Yun-Hyok (2020)
The inorganic halide perovskite CsPbI3 has shown great promise for efficient solar cells, but the instability of its cubic phase remains a major challenge. We present a route for stabilizing the cubic α-phase of CsPbI3 through the control of vacancy defects. Analysis of the ionic chemical potentials is performed within an ab initio thermodynamic formalism, including the effect of solution. It is found that cation vacancies lead to weakening of the interaction between Cs and PbI6 octahedra in CsPbI3, with a decrease in the energy difference between the α- and δ-phases. Under I-rich growth conditions, which can be realized experimentally, we predict that the formation of cation vacancies can be controlled. Other synthetic strategies for cubic-phase stabilization include the growth of nanocrystals, surface capping ligands containing reductive functional groups, and extrinsic doping. Our analysis reveals mechanisms for polymorph stabilization that open a new pathway for structural control of halide perovskites.